The combination of mesenchymal stem cells and a bone scaffold in the treatment of vertebral body defects - Vaněček, Václav; Klíma, Karel; Kohout, Aleš; Foltán, René; Jiroušek, Ondřej; Šedý, Jiří; Štulík, Jan; Syková, Eva; Jendelová, Pavla (European spine journal, 2013)
PURPOSE: Vertebral body defects represent one of the most common orthopedic challenges. In order to advance the transfer of stem cell therapies into orthopedic clinical practice, we performed this study to evaluate the safety and efficacy of a composite bioartificial graft based on a hydroxyapatite bone scaffold (CEM-OSTETIC(®)) combined with human mesenchymal stem cells (MSCs) in a rat model of vertebral body defects. METHODS: Under general isoflurane anesthesia, a defect in the body of the L2 vertebra was prepared and left to heal spontaneously (group 1), implanted with scaffold material alone (group 2), or implanted with a scaffold together with 0.5 million MSCs (group 3) or 5 million MSCs (group 4). The rats were killed 8 weeks after surgery. Histological and histomorphometrical evaluation of the implant as well as micro-CT imaging of the vertebrae were performed. RESULTS: We observed a significant effect on the formation of new bone tissue in the defect in group 4 when compared to the other groups and a reduced inflammatory reaction in both groups receiving a scaffold and MSCs. We did not detect any substantial pathological changes or tumor formation after graft implantation. CONCLUSIONS: MSCs in combination with a hydroxyapatite scaffold improved the repair of a model bone defect and might represent a safe and effective alternative in the treatment of vertebral bone defects.
Keywords: hojení ran; náhodné rozdělení; Tissue Engineering; transplantace kostí; Durapatite; Humans; Radiography; tkáňové inženýrství; Lumbar Vertebrae; Spinal Injuries; radiografie; Mesenchymal Stem Cell Transplantation; Tissue Scaffolds; krysa rodu Rattus; poranění páteře; lidé; zvířata; Wound Healing; potkani Wistar; bederní obratle; transplantace mezenchymálních kmenových buněk; tkáňové podpůrné struktury; Rats, Wistar; Male; hydroxyapatit; Rats; Animals; mužské pohlaví; Disease Models, Animal; Random Allocation; Bone Transplantation; modely nemocí na zvířatech